Design, Synthesis and Evaluation of Light-Activatable Organic Molecules that Target-Selectively Degrade DNA, Proteins and Carbohydrates; an Interdisciplinary Challenge for a Synthetic Organic Chemist - Toshima, Kazunobu (Synlett, 2012)
We developed chemical methods for target-selective photodegradation of various biomacromolecules, including DNA, proteins, and carbohydrates. The DNA intercalator-carbohydrate moiety, without the enediyne structure found in the enediyne antibiotic neocarzinostatin chromophore, selectively degrades duplex DNA at guanine (G) nucleotides upon photoirradiation. Based on this finding, we designed and synthesized several artificial DNA intercalator-carbohydrate hybrids that can be photoactivated. Among them, several quinoxaline–carbohydrate hybrids were found to photodegrade duplex DNA at the G on the 5′ side of 5′-GG-3′ sites. For protein degradation, we designed and synthesized several 2-phenylquinoline–steroid hormone hybrids and a porphyrin derivative, both of which selectively photodegrade the transcription factor estrogen receptor-α. In addition, we designed and synthesized fullerene–sugar and fullerene–sulfonic acid hybrids that selectively photodegrade HIV-1 protease and amyloid β, respectively. For carbohydrate degradation, we designed and synthesized anthraquinone–lectin hybrids and anthraquinone– and fullerene–boronic acid hybrids for selective photodegradation of target oligosaccharides having affinity for the lectin or boronic acid moiety of the hybrids. Furthermore, we successfully demonstrated practical uses for these light-activatable and molecular-targeted (LAMTA) molecules for controlling the function of DNA, proteins, and carbohydrates both in glass vessels and in cells. 1 Introduction2 DNA Photodegrading Organic Molecules2.1 DNA Intercalator–Carbohydrate Hybrids2.2 Neocarzinostatin DNA Intercalator–Carbohydrate Hybrids for DNA Photodegradation2.3 Quinoxaline-Carbohydrate Hybrids for DNA Photodegradation3 Protein Photodegrading Organic Molecules3.1 Quinoline–Steroid Hormone Hybrids for ER-α Photodegradation3.2 Fullerene–Carbohydrate Hybrids for HIV-1 Protease Photodegradation3.3 Fullerene–Sulfonic Acid Hybrid for Amyloid β Photodegradation4 Carbohydrate-Photodegrading Organic Molecules4.1 Small Organic Molecules for Oligosaccharide Photodegradation4.2 Anthraquinone–Lectin Hybrids for Oligosaccharide Photodegradation4.3 Anthraquinone–Boronic Acid Hybrids for Oligosaccharide Photodegradation5 Conclusions
Keywords: synthetic chemical biology; photodegradation; DNA; protein; carbohydrate